Journalism at Historically Black Colleges and Universities - Crawford II, Jerry. author. aut Link
XVI, 185 p.
Keywords: “In this much needed and timely volume, Dr. Jerry Crawford II focuses on HBCUs with journalism or communication programs that sought professional accreditation from AEJMC. Covering a nearly 40-year timespan, the book is well researched and well documented. The book is a must-read for administrators and faculty of HBCUs. It also is enlightening to scholars of predominantly white institutions and minority-serving institutions.” —Hong Cheng, Ph.D., professor and dean, School of Communication, Loyola University Chicago “In the ever-changing world of higher education, there’s no greater challenge for colleges and universities than to offer a credible, respected, dollar-worthy degree and accreditation provides that valuable stamp of approval. Journalism at Historically Black Colleges and Universities-Governance and Accreditation offers a valuable, thoughtful perspective on the myriad challenges faced by minority-servinginstitutions today to earn and maintain that accreditation.” —Barbara Hines, Professor Emerita, Howard University Historically Black Colleges and Universities (HBCUs) are facing challenges to their continued existence on several fronts. One is fiscally, as federal funding for education has been cut and the responsibility for paying for higher education has been levied on students and parents. This book explores journalism accreditation at HBCUs and is informed by many years of research into how journalism units have acquired and lost accreditation. It will be of interest to faculty, students and administrators of journalism studies. Jerry Crawford II is an Associate Professor and the Director of the Multicultural Program in the William Allen White School of Journalism at the University of Kansas. He teaches graduate and undergraduate classes consisting of mass media theory, ethics, multimediareporting, and special topics. Dr. Crawford has published over 20 peer-reviewed journal articles, book chapter, and conference proceedings (combined) and has presented his work at over a dozen conferences – receiving paper awards. He has served in several capacities in AEJMC, including being a member of the board of directors.